Morphology and reactivity of aluminium nanocrystalline powders. (7th February 2012) - André, Bérangère; Coulet, Marie–Vanessa; Dumont, Myriam; Rogez, Jacques; Heresanu, Vasile; Rufino, Benoit; Bouchet, Renaud; Denoyel, Renaud
Aluminium powders obtained by mechanical milling are characterised in terms of morphology, nanostructure and thermal properties. Platelets like particles with a thickness in the micrometre range are obtained. It is shown that these platelets are constituted of many nanocrystallites whose size governs the melting behaviour of the powders. Their reactivity towards oxygen is compared with that of spherical particles. Samples obtained by mechanical milling start to be oxidised at a higher temperature the amount of oxidised material is higher than that in the case of spherical particles having the same surface area. Both the thermal behaviour and the reactivity could be explained by the presence of alumina at the grain boundaries. This work shows that the milling process appears as a good alternative to gas condensation methods or wire electro–explosion processes to prepare highly reactive particles.